Drooms Store Strategy To Win Business Competition On E-Commerce Lazada - Asep Sugara; MD Sukamto; Rida Ramdani (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
This study aims to determine the Droom Store strategy in winning business competition in Lazada E-Commerce and increasing customer satisfaction. The analytical approach used is to use a qualitative approach. Where the owner of Drooms Store used as key informants with data collection using triangulation techniques. The results of research at Drooms Store using the techniques above, strategies that can win business competition in Lazada E-Commerce are product selection strategies which are the basis of product sales in which there are product research activities, namely where the seller determines the scale of the benefits of a product. product, then the price of the product, and also the target market. Product advertising strategy which is the second stage after the product selection strategy where this product advertising strategy can reach consumers and attract consumers to buy products. Then there is a product promotion strategy that aims to boost sellers to increase. A business analysis strategy that aims to control the business at Drooms Store . In other words, Lazada's E-commerce for the strategy that we will use has been very well supported by Lazada